ANALISIS KUALITAS LAYANAN WEBSITE DISDUKCAPIL KABUPATEN SEMARANG DIUKUR MENGGUNAKAN INSTRUMEN WEBQUAL 4.0 - Putra, Andree Eka; Nataliani, Yessica (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The Department of Population and Civil Registration organizes and publishes all matters relating to population. The existence of a service information system is a method used by Disdukcapil Semarang Regency to implement e-government, namely through the website http://dukcapil.semarangkab.go.id. Testing is needed for website user satisfaction using Webqual 4.0 as a website quality assessment instrument. The goal of this study is to get an overview of the influence/impact of the three website quality dimensions: usability, information, and service interaction qualities on user satisfaction. This study used 60 data tested by validity, reliability, multiple linear regression, t-test, and F-test. The results showed that the usability and information qualities affects user satisfaction, but the service interaction quality does not. In addition, the research found that the three dimensions of website quality together did not affect user satisfaction. They affect 39.2% of user satisfaction, while other factors outside the variables studied influence the other 60.8%.